Trait‐dependent distributional shifts in fruiting of common British fungi. Issue 1 (27th September 2017) - Gange, A. C.; Heegaard, E.; Boddy, L.; Andrew, C.; Kirk, P.; Halvorsen, R.; Kuyper, T. W.; Bässler, C.; Diez, J.; Heilman‐Clausen, J.; Høiland, K.; Büntgen, U.; et al.
Abstract : Despite the dramatic phenological responses of fungal fruiting to recent climate warming, it is unknown whether spatial distributions of fungi have changed and to what extent such changes are influenced by fungal traits, such as ectomycorrhizal (ECM) or saprotrophic lifestyles, spore characteristics, or fruit body size. Our overall aim was to understand how climate and fungal traits determine whether and how species‐specific fungal fruit body abundances have shifted across latitudes over time, using the UK national database of fruiting records. The data employed were recorded over 45 yr (1970–2014), and include 853 278 records of Agaricales, Boletales and Russulales, though we focus only on the most common species (with more than 3000 records each). The georeferenced observations were analysed by a Bayesian inference as a Gaussian additive model with a specification following a joint species distribution model. We used an offset, random contributions and fixed effects to isolate different potential biases from the trait‐specific interactions with latitude/climate and time. Our main aim was assessed by examination of the three‐way‐interaction of trait, predictor (latitude or climate) and time. The results show a strong trait‐specific shift in latitudinal abundance through time, as ECM species have become more abundant relative to saprotrophic species in the north. Along precipitation gradients, phenology was important, in that species with shorter fruiting seasons have declined markedly in abundance in oceanic regions, whereas species with longer seasons have become relatively more common overall. These changes in fruit body distributions are correlated with temperature and rainfall, which act directly on both saprotrophic and ECM fungi, and also indirectly on ECM fungi, through altered photosynthate allocation from their hosts. If these distributional changes reflect fungal activity, there will be important consequences for the responses of forest ecosystems to changing climate, through effects on primary production and nutrient cycling.